Islamic Dynamics in Indonesia - Busman Edyar (Institut Agama Islam Negeri (IAIN) Curup, 2016)
In contrast to countries in Southeast Asia such as Malaysia, Singapore, Brunei Darussalam, and even Thailand, Islam in Indonesia has special characteristics. If these countries have a homogeneous tendency, on the other hand Indonesia is very heterogeneous. The strong hegemony of the authority of the religious life, tend to become a reason for the emergence of a monolithic color in religious life. Otherwise, in Indonesia, the strong pull of the relationship between Islam and the country it self, led to religious practice that necessitates the diversity, the denial of the diversity. The following article examines the religious diversity which apparent since Indonesia emerged as a country. Keywords: dynamics, Islam, Indonesia